Pengenalan bunyi vokal Indonesia berbasis jaringan saraf tiruan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT: This paper deals with an application of an artificial neural network (ANN) for Indonesian vowel sound recognition. A threelayer backpropagation neural network is used for this classification problem. The ANN is trained to recognize Indonesian vowel sound by entering its feature to the network The lowest and highest recognition correspondingly 75% for /e/ sound and 87% for /a/ sound Other sounds can be recognized in the range between 75% to 87%